Extreme right activists in Europe : through the magnifying glass - Klandermans, Bert; Mayer, Nonna (Routledge studies in extremism and democracy ;, 2006)
Since the 1980s, one of the main political changes in Western Europe has been the electoral upsurge of extreme right-wing parties. However, while the electoral support of these movements has been studied extensively, their membership has largely been ignored. This book examines who joins the extreme right and why?Drawing upon extensive research and featuring contributions from distinguished social psychologists and political scientists, this book provides the most detailed comparative study yet published of the psychology of right-wing extremist activists. Countries discussed include G.